"Be the leader", or "Everything is to your pocket": Comparative Description of the Moscow Advertisement in the Metro and Outdoor Advertising - ДобряковаМария Сергеевна; НадеждинаЕвгения Владимировна (Journal of Economic Sociology, 2010)
Detailed description in the text